Estimation of salivary and serum CYFRA 21-1 levels in patients with oral squamous cell carcinoma - Adusumilli, Praveena; Babburi, Suresh; Venigalla, Aparna; Benarji, Kotti; Sai, Surapaneni; Soujanya, Pinisetti (Journal of oral and maxillofacial pathology : JOMFP, 2023)
Background: Cytokeratins are the largest sub-group of intermediate filaments and represent the most abundant proteins in epithelial cells. CYFRA 21-1 (human cytokeratin fragment antigen 21-1) is a soluble fragment of cytokeratin 19 known to increase in various malignancies. Aim: The present study is aimed to estimate salivary and serum levels of CYFRA 21-1 in oral squamous cell carcinoma (OSCC) patients and to compare them with healthy controls. Settings and Design: A prospective, case-control study. Material and Methods: This study included a total of 80 subjects, comprising 40 OSCC patients and 40 healthy controls. Saliva and blood samples were collected from the study population, and serum and salivary CYFRA 21-1 levels were measured by enzyme-linked immunosorbent assay. Statistical Analysis Used: The statistical tests applied were independent t-test, ANOVA test for comparison, and Post hoc test for correlation. A P value of < 0.05 was considered statistically significant. Results: A statistically significant increase in salivary and serum CYFRA 21-1 levels was observed between OSCC and control groups and with an increase in the pathological tumour node metastasis stage and histopathological grade of OSCC. On correlating salivary and serum CYFRA 21-1 values, there were 3-fold higher salivary levels than serum. Conclusion: CYFRA 21-1 can be suggested as a tumour marker that can be used for the early diagnosis of the OSCC. Further prospective studies with a larger sample size and advanced techniques recommended before CYFRA 21-1 can be recommended for routine clinical use.